Simple Spectrophotometric Methods for the Determination of Zidovudine in Pharmaceuticals Using Chloramine-T, Methylene Blue and Rhodamine-B as Reagents - K. Basavaiah; U. R. Anil Kumar (E-Journal of Chemistry)
Two new spectrophotometric methods are proposed for the determination of zidovudine(ZDV) in pharmaceuticals. The methods use chloramine-T (CAT) and two dyes, methylene blue and rhodamine-B, as reagents and are based on adding of a known excess of CAT to ZDV in hydrochloric acid medium followed by determination of residual oxidant by reacting with a fixed amount of either methylene blue and measuring the absorbance at 665 nm (Method A) or rhodamine B and measuring the absorbance at 555 nm (Method B). In both methods, the amount of CAT reacted corresponds to the amount of ZDV. The absorbance measured is found to increase linearly with concentration of ZDV. Under the optimum conditions, ZDV could be assayed in the concentration range 1.25-15.0 and 0.25-3.0 μg ML-1 by method A and method B, respectively. The apparent molar absorptivities are calculated to be 7.7x103 and 5.6x104 L mol-1 cm-1 for method A and method B, respectively, and the corresponding Sandell sensitivity values are 0.035 and 0.005 μg cm-2. The limits of detection and quantification are reported for both methods. Intra-day and inter-day precision and accuracy of the developed methods were evaluated as per the current ICH guidelines. The proposed methods can be readily utilized for bulk drug and in pharmaceutical formulations.